The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.22215/timreview/1354
|View full text |Cite
|
Sign up to set email alerts
|

Citizen Perceptions of Government’s Resistance to Shared Parking

Abstract: CBC News explicit what is legal and what is illegal (Uzunca & Borlenghi, 2019).According to Hofmann et al. (2019), there is a need to understand the tensions between citizen users and the authorities, which have arisen from government's negative attitude toward sharing economies. Further, prior studies (for example, May et al., 2017;Ganapati & Reddick, 2018), call for more research on the barriers and opportunities related to specific sectors and integrations of sharing economies. In urban research, shared mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The comments were most frequently between one and 50 words, with an emphasis on the range between four and 30 words. These results are in line with those of previous research using online posts ( Westerlund 2020 ). For example, Sobkowicz et al (2013) found that the message-length distributions of various forms of Internet-based written communications follow a similar pattern.…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…The comments were most frequently between one and 50 words, with an emphasis on the range between four and 30 words. These results are in line with those of previous research using online posts ( Westerlund 2020 ). For example, Sobkowicz et al (2013) found that the message-length distributions of various forms of Internet-based written communications follow a similar pattern.…”
Section: Methodssupporting
confidence: 93%
“…We applied topic modelling, a probabilistic machine-learning method that discovers hidden thematic structures, by means of a group of inductive computational techniques, in a large corpus of documents, in our case common topics in small business owner narratives ( Hannigan et al 2019 ; Kim and Chen 2018 ; Westerlund 2020 ). Topic modelling uses statistical associations of words in a text to generate latent topics on the basis of co-occurring words that jointly represent higher-order concepts, without the aid of predefined, explicit dictionaries or interpretive rules; hence, topic modelling is an unsupervised approach ( Hannigan et al 2019 ; Murakami et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation